Youth and Expectations on Democracy in Spain: the Role of Individual Human Values Structure of Young People in Dimension of Democracy - Carratalà Puertas, Liberto; Frances Garcia, Francisco José (PARTECIPAZIONE E CONFLITTO, 2017)
Democracy is a form of social organization based on popular sovereignty. The rise of democracy has run in parallel to economic growth in society and this system of government has been increasingly adopted in other countries (Inglehart, 2005). The same concept has been defined over time in different ways according to their historical characteristics. According to Kluckhohn (1958), humans react to external stimuli as well as to their own interpretations of stimuli as per a cognitive framework defined by the cul-ture in which the individual is inserted. This research is aimed at learning how values influence the concept that young Spaniards have of democracy and determine how these affect each dimension, factor or element in which the study of this type of social organization can be divided. In order to carry out this research we are using data from the sixth round of the European Social Survey (ESS) conducted in 2012. The sample consists of two groups, one with individuals aged 18 to 30 and a second group with people over 30 years of age. Results indicate that democracy —and its elements— is not an ideal concept, or it should not be seen as an invariable, objective concept, external to citizens. It is rather an adaptive and evolving instrument, consubstantial to each individual’s vital experience and society’s in its whole in which values have a joint function between the macro and the micro-social groups.